2020
DOI: 10.3847/2041-8213/ab7244
|View full text |Cite
|
Sign up to set email alerts
|

Fast Radio Bursts from Interacting Binary Neutron Star Systems

Abstract: Recent observations of repeating fast radio bursts (FRBs) suggest that some FRBs reside in an environment consistent with that of binary neutron star (BNS) mergers. The bursting rate for repeaters could be very high and the emission site is likely from a magnetosphere. We discuss a hypothesis of producing abundant repeating FRBs in BNS systems. Decades to centuries before a BNS system coalesces, the magnetospheres of the two neutron stars start to interact relentlessly. Abrupt magnetic reconnection accelerates… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 72 publications
0
36
0
Order By: Relevance
“…The physical origins of FRBs are still mysterious. The observed short timescale structure in FRB light curves requires stellar-mass compact objects as central engines, such as magnetars (Popov & Postnov 2013;Kulkarni et al 2014;Murase et al 2016;Metzger et al 2017;Beloborodov 2017;Margalit et al 2018), binary neutron stars mergers (Totani 2013;Wang et al 2016;Yamasaki et al 2018;Zhang 2020), and interacting models (Geng & Huang 2015;Dai et al 2016;Zhang 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The physical origins of FRBs are still mysterious. The observed short timescale structure in FRB light curves requires stellar-mass compact objects as central engines, such as magnetars (Popov & Postnov 2013;Kulkarni et al 2014;Murase et al 2016;Metzger et al 2017;Beloborodov 2017;Margalit et al 2018), binary neutron stars mergers (Totani 2013;Wang et al 2016;Yamasaki et al 2018;Zhang 2020), and interacting models (Geng & Huang 2015;Dai et al 2016;Zhang 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [217] have shown that if there is any association between compact binary coalescence and (catastrophic) FRBs, it should only apply for a very small fraction of FRBs. There is a possibility that repeating FRBs are produced by continuous magnetosphere interactions between two neutron stars [218]. If so, a connection might be made between repeating FRBs and Laser Interferometer Space Antenna (LISA) GW sources.…”
Section: Future Prospectsmentioning
confidence: 99%
“…The ms periodicity may suggest a misclassified galactic pulsar origin, but the DM of the source strongly points towards an extragalactic source. One intriguing explanation for this behaviour in the context of non-repeating FRBs is the generation of periodic pulses from merging neutron stars, with the production of FRBs originating from the interaction from their magnetospheres long before the merger [53].…”
Section: Frb Profilesmentioning
confidence: 99%